Investigating the Association Between University Teachers’ Professional Autonomy and Their Innovation Performance - Gavrilyuk, Oksana A.; Tareva, Elena G.; Lakhno, Anastasiya V. (Pedagogika, 2019)
The purpose of this paper is to investigate both - theoretical and practical aspects in association between foreign language teachers’ professional autonomy and their innovation performance under the current educational circumstances. The findings demonstrate that the development of innovative university teachers is possible in the framework of the autonomy-oriented approach that gets the teachers to be involved in intensive analysis and project activity, based on an analysis and a review of teachers’ personal learning and professional experience in a wide range of educational context.